2011
DOI: 10.5539/ibr.v4n2p183
|View full text |Cite
|
Sign up to set email alerts
|

What Drives Student Loyalty in Universities: An Empirical Model from India

Abstract: Student loyalty is one of the major goals of educational institutions. A loyal student population is a source of competitive advantage. The specific objective of this research was to develop an empirical model linking student loyalty to student satisfaction and student perception of the reputation of the institution. Based on the data collected from students with leading universities in India, a structural model was developed explaining 57.7% of the variance in the student loyalty. The student satisfaction was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 51 publications
2
78
0
12
Order By: Relevance
“…A number of researchers (see for example, [14], [16], [17], [19]) have confirmed that with the appropriate number of well-equipped computer labs and technical support, student satisfaction at business schools is greatly enhanced. The Computer Center at CBA supervises and maintains six computer labs consisting of over 200 computers and laser printers, provides on-demand technical assistance and training to students, provides all lecture halls, offices, and student clubs with high-speed internet, oversees the financial dealing rooms, provides Wi-Fi service to the campus, and maintains classroom technology installed in each lecture hall.…”
Section: ) Computer Labs Dealing Room Satisfactionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of researchers (see for example, [14], [16], [17], [19]) have confirmed that with the appropriate number of well-equipped computer labs and technical support, student satisfaction at business schools is greatly enhanced. The Computer Center at CBA supervises and maintains six computer labs consisting of over 200 computers and laser printers, provides on-demand technical assistance and training to students, provides all lecture halls, offices, and student clubs with high-speed internet, oversees the financial dealing rooms, provides Wi-Fi service to the campus, and maintains classroom technology installed in each lecture hall.…”
Section: ) Computer Labs Dealing Room Satisfactionmentioning
confidence: 99%
“…Seng and Ling [11], mention that the students who participate in student organizations, interacting with faculty members and other students are more likely to have a higher level of satisfaction than those who do not. Thomas [14] found that the second most important factor driving student satisfaction was social networking with peers and close working relationships with other students.…”
Section: International Journal Of Information and Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…Sembiring, 2013;Kheiry et al, 2012;Thomas, 2011;Mohamad & Awang, 2009). What is missing in the customer loyalty research in the educational sector is the kind of behavioural attitude employees of educational institutions, especially universities which the study is focused, should demonstrate towards their students for them to be loyal.…”
Section: Introductionmentioning
confidence: 99%